Study on Hamster Mice Served as an Experimentally Paratenic Host of Spirometra Tapeworm - Kavana, Nicholas J. (Contemporary Research and Perspectives in Biological Science Vol. 3, 2024)
Hamster mice are a good laboratory model for a second intermediate host in the life cycle of Spirometra species. A total of 10 hamster mice were experimentally fed orally in the laboratory with Spirometra spargana collected from naturally infected frogs (R. cancrivora) from the rice fields. A total of 22 spargana were used to infect 10 Hamster mice. On the 30th and 120th days post-infection, Hamster mice were sacrificed and spargana were recovered. A total of 15 spargana were recovered from 9 hamster mice and one hamster mouse was negative. Sites of predilection were the neck, axilla and chest. Measurements of the recovered spargana were on an average length of 80-170 mm on the 120th day post-infection. Spirometra spargana were maintained in the Hamster mice for 120 days, this indicates that Hamster mice are a good laboratory model for a second intermediate host in the life cycle of Spirometra species.